Evaluasi Program ‘Yuk Nabung Saham oleh PT. Bursa Efek Indonesia Terhadap Peningkatan Literasi dan Inklusi Keuangan di Kota Jambi - Sugeng Haryono; Deka Veronica (J-MAS (Jurnal Manajemen dan Sains), 2020)
The growth of investors in the Indonesian capital market as one of the alternatives to public investment is considered quite good Indonesia Stock Exchange (IDX) as the manager of securities sales in Indonesia continues to make efforts to improve the understanding of public investment in the capital market. One of them is by increasing the number of Bank Administrator Of Customer's Fund Account (BANK RDN) and at this time IDX is eager to make the introduction of the program "Yuk Nabung Saham". This program is a campaign that invites indonesians to invest in the capital market through "share saving". This research aims to test the influence of the "Yuk Nabung Saham" program on improving financial literacy and inclusion in economic studies students in universities in Jambi cities who have met the sample criteria. Based on the research results of the campaign program "Yuk Nabung Saham" has a positive effect on the increase in financial literacy and inclusion in students in Jambi city means that if someone follows the program then literacy will be more increased and financial inclusion will be easier to obtain in addition to the campaign program "Yuk Nabung Saham" has a positive impact on the increasing number of stock investors, especially students in Jambi city, meaning if the YNS program goes well and can manage it , the greater the level of student financial inclusion.